STUDENT SATISFACTION WITH EDUCATION: DIAGNOSTIC TECHNIQUES AND INTERRELATED FACTORS - Mamadjanova Madina Aleksandrovna (Galaxy International Interdisciplinary Research Journal, 2024)
In international contexts, student satisfaction stands as a crucial indicator of higher education quality. Evaluations primarily focus on specific aspects of the educational process rather than the subjective state of students. It is imperative to diagnose satisfaction as a key manifestation of the inner world and experiences of the individual in the field of psychology. From a practical perspective, the study of student satisfaction with education serves as a vital tool to assess and improve the quality of education and to enhance psychological support at both the individual and group levels. Furthermore, it serves as a direct indicator of the efficacy of interventions aimed at unleashing the personal potential of students. It’s important to note that the development of techniques for measuring subjective indicators of higher education quality primarily relies on the iden-subject approach and studies of personal potential.